Clinical Comparison of Epidural Clonidine and Verapamil with Ropivacaine in Abdominal Hysterectomy; A Prospective, Randomized, Controlled Study. - Suraj Kumar; Manoj Tripathi; Deepak Malviya; Sujeet Rai; Sumit Kumar; Manoj Kumar Giri (Academia Anesthesiologica International, 2020)
Background: Adjuvants, when combined with local anaesthetics, increase duration of block, improve quality of blockade and accelerate onset of block. The aim of this study is to assess the analgesic properties and postoperative analgesia of Clonidine and verapamil in the epidural block for abdominal hysterectomy.Subjects and Methods:Ninety patients were divided into three groups Group l- patient were given ropivacaine (0.75%) in the dose of 20 ml, Group II -0.75% ropivacaine 20 ml with verapamil in the dose of 2.5 ml, Group III -0.75% ropivacaine 20 ml with Clonidine in the dose of 1mcg/kg body weight. Patients were assessed for onset, degree, level, duration of sensory and motor block, duration of complete analgesia and postoperative analgesia, rescue analgesic requirement, sedation score and adverse effects.Results:When groups I and II were compared, onset of sensory and motor block was found to be statistically insignificant (p>0.05), while it was early in group III in comparison to groups I and II and statistically significant ( p<0.05). The duration of sensory block in group III was more in comparison to groups I and II  and were statistically significant ( p<0.05). The mean duration of analgesia in group I was 184.03 + 5.20 mins, in group II was 300.46 + 5.80 mins and in groups, III was 538 + 12.80 mins.Conclusion:Verapamil does not enhance the onset, duration of the sensory and motor block, though Clonidine in the dose of 1ug/kg enhances the onset of sensory block. The duration of postoperative analgesia with verapamil was more and much higher compared to Clonidine.